Development of a modified QuEChERS method based on magnetic multiwalled carbon nanotubes for the simultaneous determination of veterinary drugs, pesticides and mycotoxins in eggs by UPLC-MS/MS. (15th March 2019) - Xu, Xu; Xu, Xiaoying; Han, Mei; Qiu, Shiting; Hou, Xue
Highlights: A modified QuEChERS-UPLC-MS/MS method was used for multi-residue analysis in eggs. The modified QuEChERS method was developed using Fe3 O4 -MWCNTs as adsorbents. Magnetic separation simplified the sample pretreatment and allowed rapid analysis. Good accuracy and precision as well as low LOQs were obtained for most compounds. Abstract: A modified QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) method was developed for the simultaneous determination of veterinary drugs, pesticides and mycotoxins in eggs by ultrahigh-pressure liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Several extraction conditions were tested and optimized, and the obtained extraction efficiency of all the targeted compounds (particularly macrolides) could fulfill the requirements. In the purification procedure, magnetic multiwalled carbon nanotubes (Fe3 O4 -MWCNTs) were used as adsorbents, and an external magnet was utilized to achieve a faster adsorbent separation, compared to the traditional centrifugation process. The recoveries of all analytes were in the range of 60.5%–114.6% at three fortified levels with relative standard deviations (RSDs) of less than 20%, and the LOQs ranged from 0.1 μg·kg −1 to 17.3 μg·kg −1 . This method was successfully applied to the analysis of egg samples, demonstrating its applicability and suitability for the routine analysis of multiclass residues in egg samples.